Updating M6 pregnancy of unknown location risk‐prediction model including evaluation of clinical factors - Kyriacou, C.; Ledger, A.; Bobdiwala, S.; Ayim, F.; Kirk, E.; Abughazza, O.; Guha, S.; Vathanan, V.; Gould, D.; Timmerman, D.; Van Calster, B.; Bourne, T.; et al. (Ultrasound in obstetrics & gynecology, 2024)
ABSTRACT Objectives Ectopic pregnancy (EP) is a major high‐risk outcome following a pregnancy of unknown location (PUL) classification. Biochemical markers are used to triage PUL as high vs low risk to guide appropriate follow‐up. The M6 model is currently the best risk‐prediction model. We aimed to update the M6 model and evaluate whether performance can be improved by including clinical factors. Methods This prospective cohort study recruited consecutive PUL between January 2015 and January 2017 at eight units (Phase 1), with two centers continuing recruitment between January 2017 and March 2021 (Phase 2). Serum samples were collected routinely and sent for β‐human chorionic gonadotropin (β‐hCG) and progesterone measurement. Clinical factors recorded were maternal age, pain score, bleeding score and history of EP. Based on transvaginal ultrasonography and/or biochemical confirmation during follow‐up, PUL were classified subsequently as failed PUL (FPUL), intrauterine pregnancy (IUP) or EP (including persistent PUL (PPUL)). The M6 models with (M6P) and without (M6NP) progesterone were refitted and extended with clinical factors. Model validation was performed using internal–external cross‐validation (IECV) (Phase 1) and temporal external validation (EV) (Phase 2). Missing values were handled using multiple imputation. Results Overall, 5473 PUL were recruited over both phases. A total of 709 PUL were excluded because maternal age was < 16 years or initial β‐hCG was ≤ 25 IU/L, leaving 4764 (87%) PUL for analysis (2894 in Phase 1 and 1870 in Phase 2). For the refitted M6P model, the area under the receiver‐operating‐characteristics curve (AUC) for EP/PPUL vs IUP/FPUL was 0.89 for IECV and 0.84–0.88 for EV, with respective sensitivities of 94% and 92–93%. For the refitted M6NP model, the AUCs were 0.85 for IECV and 0.82–0.86 for EV, with respective sensitivities of 92% and 93–94%. Calibration performance was good overall, but with heterogeneity between centers. Net Benefit confirmed clinical utility. The change in AUC when M6P was extended to include maternal age, bleeding score and history of EP was between −0.02 and 0.01, depending on center and phase. The corresponding change in AUC when M6NP was extended was between −0.01 and 0.03. At the 5% threshold to define high risk of EP/PPUL, extending M6P altered sensitivity by −0.02 to −0.01, specificity by 0.03 to 0.04 and Net Benefit by −0.005 to 0.006. Extending M6NP altered sensitivity by −0.03 to −0.01, specificity by 0.05 to 0.07 and Net Benefit by −0.005 to 0.006. Conclusions The updated M6 model offers accurate diagnostic performance, with excellent sensitivity for EP. Adding clinical factors to the model improved performance in some centers, especially when progesterone levels were not suitable or unavailable. © 2023 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology.